Fly on the wall – attachment structures in lower Diptera. (July 2014) - FRIEDEMANN, KATRIN; SCHNEEBERG, KATHARINA; BEUTEL, ROLF G.
Abstract Pretarsal attachment structures of representatives of the megadiverse Diptera are examined and documented, mainly using scanning electron microscopy. The focus is on the basal 'nematoceran' lineages. The diversity in structures is much higher than suggested by brief summarizing accounts in earlier studies. Both hairy and smooth attachment structures occur. A well‐developed, pad‐like empodium with its ventral surface covered with adhesive hairs is arguably a groundplan feature of Diptera. Very often this pad is combined with the presence of hairy pulvilli. However, smooth pulvilli occur in two of the examined groups. A smooth arolium is present in Tipulomorpha and likely an autapomorphy of this clade, suggesting that it was acquired secondarily. Evolutionary transformations are interpreted based on recently published dipteran phylogenies.